Simulation of tendon energy storage in pedaling - Rasmussen, J.; Damsgaard, M.; Christensen, S. T. (2001)
The role of elastic energy stored in tendonsduring pedaling is investigated by means of numerical simulationusing the AnyBody body modeling system. Theloss of metabolic energy due to tendon elasticity is computed and compared to the mechanical work involved in the process. The Any Body simulation system is based on inverse dynamics, where the redundancy problem issolved by a minimum fatigue criterion guaranteeing maximum inter-muscular collaboration. The tendons areassumed to be linearly elastic. It is concluded that tendon elasticityis responsible for metabolic power loss, and that the movement strategy is influenced by the presence of elasticity.